PERKEMBANGAN KEBIJAKAN PEMBIAYAAN INFRASTRUKTUR TRANSPORTASI BERBASIS KERJASAMA PEMERINTAH SWASTA DI INDONESIA - Susantono, Bambang; Ali Berawi, Mohammed (Jurnal Transportasi, 2012)
Transportation infrastructure development is one of the vital aspects needed to improve the economic growth of a country. In Indonesia, transportation infrastructure development in the next 15 years requires an estimated investment of IDR 1,785 trilion. This figure includes IDR 339 trilion investment for roads, IDR117 trilion for ports, IDR 32 trilion for airports, and IDR 326 trilion for railways. Public Private Partnership (PPP) approach is used in the infrastructure development program as an alternative to finance transportation infrastructure projects in Indonesia. This paper aims to discuss the historical development of PPP policy inIndonesia in an effort to create Value for Money in the infrastructure development projects. Furthermore, various studies on the key success factors of successful implementation of PPP schemes in other countries and the strategic action from Indonesian government to produce a range of policies that support the implementation of the PPP scheme since 1998-2012 are also discussed.Keywords: Public Private Partnership, transportation infrastructure, project financing.